2015
DOI: 10.1007/s00170-015-7381-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on the influence of the jet parameters of minimum quantity lubrication on the lubricating property of Ni-based alloy grinding

Abstract: Based on research on nanofluid minimum quantity lubrication (MQL) in grinding, a plane grinding experiment was performed on Ni-based alloy using a K-P36 precision numerical control surface grinder. Uniform grinding parameters were used in the experiment, but three groups of MQL jet parameters were changed. The grinding force was measured using a YDM-III99 three-dimensional dynamometer to calculate the specific grinding energy and coefficient of friction. The surface roughness of the workpiece was measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Ordinarily, the main disadvantage of the precision injection mold is that the mold service life was limited by the characteristics of injection mold materials. Therefore, some reinforcing additives, such as wollastonite, molybdenum disul de [39][40][41], silica sand, glass sphere, zirconia [42][43][44], silicon nitride [45][46][47], or silica sand were recommended for adding to the injection mold. In this study, the injection mold was employed in wax injection molding for manufacturing precision wax patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Ordinarily, the main disadvantage of the precision injection mold is that the mold service life was limited by the characteristics of injection mold materials. Therefore, some reinforcing additives, such as wollastonite, molybdenum disul de [39][40][41], silica sand, glass sphere, zirconia [42][43][44], silicon nitride [45][46][47], or silica sand were recommended for adding to the injection mold. In this study, the injection mold was employed in wax injection molding for manufacturing precision wax patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Single-step nanofluid preparation method is to disperse nanoparticles in base fluid while preparing them, which then saves the problems like nanoparticle collection and storage and can effectively avoid the oxidizing reaction of metal nanoparticles in atmosphere. This method is of high cost and small preparation quantity, and it is not suitable for actual batch application in production [6]. Two-step nanofluid preparation method is to add a certain proportion of nanoparticles in base fluid and select corresponding surface dispersant together with supersonic vibration according to physical and chemical properties so that nanoparticles can be distributed uniformly and stably in base fluid and nanofluid with suspension stability will be formed [27].…”
Section: Nanofluid Minimum Quantity Lubrication Cooling Technique 21mentioning
confidence: 99%
“…Yang et al [44] investigated the critical maximum undeformed equivalent chip thickness for ductile-brittle transition (DBh max-e ) of zirconia ceramics under different lubrication conditions and found that lubrication condition affects the normal force and ultimately influences the resultant force on workpiece, making DBh max-e decreases with increasing friction coefficient. [6]. The maximum specific tangential grinding force and μ were obtained in dry grinding.…”
Section: A Review On the Law Of Grinding Thermodynamics 31 A Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical method to stabilize the nanofluid is to modify the NP surface The effective use of nanofluid lubricants have been also examined for other applications. For example, the lubrication performance of nanofluids for minimal quantity lubrication (MQL) in grinding processes was evaluated [71][72][73][74]. It was shown that nanoparticle-jet MQL achieved cooling and lubrication effects close to that of flood lubrication.…”
Section: Nanoparticles In Lubricationmentioning
confidence: 99%